Objectification of female cosplayers in Indonesian digital communities: A case study of Ai Kirishima - Azzen, Syaqrah Karara (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2025)
Female cosplayers (costume play) in Indonesian digital communities experience objectification and victim blaming, as illustrated in the case of Ai Kirishima, where online responses reinforce gender bias and moral surveillance. This study aims to critically analyze how digital discourse is constructed in cases of gender-based violence against female cosplayers, focusing on three layers of discourse: media framing, patterns of public comments, and the reproduction of legitimized violence. This study employs a qualitative approach using Fairclough’s Critical Discourse Analysis to examine media framing, public comments, and social context in the Ai Kirishima case through digital comment data analyzed thematically. This study identifies three findings: 1) social media frames the tragedy in a sensational and gender-biased manner, prioritizing virality over victim sensitivity and generating ambiguous empathy and victim blaming. 2) public comments are dominated by victim blaming, body objectification, and perpetrator justification, while empathy toward victims remains a minority. 3) digital discourse reproduces the legitimization of gender-based violence by shifting sympathy from victims to perpetrators. This study concludes that digital media reproduces systemic gender bias: media frame events sensationally, online users engage in victim blaming, and sympathy shifts toward perpetrators, thereby reinforcing the legitimization of gender-based violence. This study contributes to digital gender studies by introducing the concept of sympathy reversal, while also promoting critical gender literacy, platform reform, and victim-centered media framing.